The three-dimensional kinematics and spatiotemporal parameters of gait in 6-10 year old typically developed children in the Cape Metropole A Pilot Study - Smith, Yvonne (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScPhysio)--Stellenbosch University, 2015.